0042 What Effect Does A Medical Mentorship Programme Have On Supporting The Transition From Undergraduate Study To Becoming A Newly Qualified Doctor?. (1st November 2014) - Stirling, Kevin; Dalgaty, Faith; Guthrie, Greg; Kenny, Heather
Abstract : Background: T here is an acknowledged performance gap that students experience when transiting from academia to practice. 1 Mentorship is a core component of undergraduate teaching and is a catalyst for academic success and productivity. 2 We present findings from a pilot study designed to support the transition from undergraduate study to becoming a Foundation Doctor (FD). The Medical Mentorship Programme (MMP) supports the professional development of final year medical students via a programme of clinical mentorship and simulation based workshops. Methodology: The authors explored the perceptions of a 'gap' with FD's within NHS Tayside. FD's completed a short anonymous questionnaire which asked them to critique their experiences of becoming a doctor. The results of this questionnaire informed the development of the MMP. MMP consists of 3 workshops: Preparing to be a Mentor (For FD's only) Improving your Clinical Practice Becoming an Effective Practitioner 7 FD's were recruited to this pilot study and trained to become mentors. Each FD was allocated 2–3 medical students. These mentorship groups attended a programme of simulation workshops. To encourage skill transference, mentors then conducted teaching shifts within their clinical area. We examined the effectiveness of this approach using a modified capabilities and transference questionnaire which gathered data at specific time intervals. 3 Expected results: The pilot study will conclude in June 2014. We anticipate that the construct of the mentorship group will have a positive impact on a student's professional development. We expect that FD's will recognise the importance of effective mentorship. Conclusion: MMP has been designed to improve the confidence and capabilities of senior medical students and subsequently to be better prepared to become FD's. Our institution and external organisations are keen to explore the possibility of rolling this model out to increase patient safety, and work efficiency particularly during the early transition phase. References: Yardley S, Irvine A, Lefroy J. Minding the gap between communication skills simulation and authentic experience. Medical Education 2013;47:495–510 Sambunjak D, Straus S, Marušic´ A. Mentoring in Academic Medicine: A Systematic Review. JAMA 2006;296(9):1103–1115 The Canadian Society for Training and Development. Investing In People: Tools and Resources. [Accessed 03.06.14]